Nonlinear oscillations in systems with large static deflection of elastic elements - Nguyen Van Dao (Vietnam Journal of Mechanics)
In mechanical systems the static deflection of the elastic elements is usual not appeared in the equations of motion. The reason is that either a linear model of the elastic elements or their too small static deflection assumption was accepted.